Pengaruh Layanan Bimbingan Kelompok Terhadap Perilaku Prososial - Rini, Anik Mahtun Fajar; Sugiharto, Dwi Yuwono Puji (Universitas Negeri Semarang, 2017)
Prosocial behavior is the behavior of mutual help without expecting anything in return. There are students who already have prosocial behavior, but there are also students who lack prosocial behavior. The purpose of this research was to get information or empirical finding about effect of group guidance about prosocial behaviour the eight junior school of SMP Negeri 7 Semarang. This research is experimental research.The population was all student of the VIII class in SMP Negeri 7 Semarang. Purposive technique was used in this research, sample were 10 students. Data collection technique using prosocial scale. The data analysis technique used descriptive percentage analysis and wilcoxon match pairs analysis.the result showed the prosocial behaviour of student before student are given group guidance service is in the average medium category (55,14%) and after obtaining group guidance service have an average in the high category (79,25%). Based on wilcoxon showed Zacount0 and Ztable=8. The conclusion of this research was guidance group service given positive effect to prosocial behavior student VIII class SMP Negeri 7 Semarang.